2002
DOI: 10.1051/0004-6361:20020737
|View full text |Cite
|
Sign up to set email alerts
|

High matter density peaks from UVES observations of QSO pairs: Correlation properties and chemical abundances

Abstract: Abstract. We study the transverse clustering properties of high matter density peaks as traced by high column density absorption systems (either Lyman limit systems characterized by N(H ) ≥ 2 × 10 17 cm −2 or C  systems with W r > 0.5 Å) at redshifts between 2 and 3 with UVES spectra of two QSO pairs (UM680/UM681 at 56 arcsec angular separation and Q2344+1228/Q2343+1232 at 5 arcmin angular separation) and a QSO triplet (Q2139-4433/Q2139-4434/Q2138-4427 at 1, 7 and 8 arcmin angular separation). We find 3 dam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 61 publications
2
38
0
Order By: Relevance
“…iii) QSO B0307-195A and B separated by ∼1 arcmin. A sub-DLA (at z = 1.788 with log N H I = 19.00 ± 0.10) along the line-of-sight of QSO B0307-195B is detected (D'Odorico et al 2002), but is not seen in its companion. iv) QSO J1039-2719 and QSO B1038-2712 separated by 17.9 .…”
Section: Lines-of-sight Of Interestmentioning
confidence: 95%
“…iii) QSO B0307-195A and B separated by ∼1 arcmin. A sub-DLA (at z = 1.788 with log N H I = 19.00 ± 0.10) along the line-of-sight of QSO B0307-195B is detected (D'Odorico et al 2002), but is not seen in its companion. iv) QSO J1039-2719 and QSO B1038-2712 separated by 17.9 .…”
Section: Lines-of-sight Of Interestmentioning
confidence: 95%
“…A full presentation of the data reduction is given in a parallel paper focussed on a study of nitrogen abundances in DLAs (Centurión et al 2003). More details on UVES studies of the systems at z = 2.812 in QSO 0528−2505 and z = 2.431 in QSO 2343+1232 can be found in Péroux et al (2003) and D'Odorico et al (2002), respectively. The column densities have been derived with the Voigt-profile fitting routines FITLYMAN (Fontana & Ballester 1995) implemented in the MIDAS software package.…”
Section: The Datamentioning
confidence: 99%
“…The system shows at least two components and the CIV λ1548−1550 doublet, SiII λ1260, SiIII λ1206 and FeII λ2382 transitions are observed in addition to a strong log(N HI ) > 15 Lyα. Coincidences of absorption systems on scales up to several arcminutes (D'Odorico et al 2002) are observed in the spectra of quasars as the signature of spatial correlation of high density peaks. In the present case the distance between the galaxy HDF-S 1432 and the absorber, 6.2 arcmin, corresponds to 3.1 proper Mpc and is suggestive of a large scale structure at z ∼ 2, which would be extremely interesting to further investigate by carrying out the identification of Lyman-break galaxies in correspondence of the HDF-S STIS field.…”
Section: High Redshift Galaxiesmentioning
confidence: 99%